UNINTENDED PREGNANCY: KNOWLEDGE AND ATTITUDE OF YOUNG ADOLESCENT - Nurina Sari Supriatna; Restuning Widiasih; Mira Trisyani (Journal of Maternity Care and Reproductive Health, 2019)
Unintended Pregnancy (KTD) is one of the adolescent health problems as the number has increased annually and impacted to adolescent, physically and psychologically. Many studies assessed adolescents' knowledge of KTD in middle and late adolescent groups. However, the study that assesses early adolescents (12-15 years) about KTD are limited. The aim of this study was to examine early adolescent knowledge and attitudes about KTD. This research was quantitative descriptive research. This study involved 373 female students in Jatinangor, West Java. Data were collected by a questionnaire that assessed adolescents' knowledge and attitude of KTD and were analyzed using statistical analysis. Results showed that teenagers' knowledge of KTD was good, and their attitudes towards KTD showed a conative attitude, adolescents have carried out behavior that might cause of KTD. Early adolescents have good knowledge about KTD, however, they knew risky behavior may happen to them. It is necessary to increase early adolescents’ awareness of KTD.  Keywords: adolescence, attitude, knowledge, unintended pregnancy.